Association of Skilled Nursing Facility Participation in Voluntary Bundled Payments With Postacute Care Outcomes for Joint Replacement. Issue 2 (12th February 2023) - Ying, Meiling; Thirukumaran, Caroline P.; Temkin-Greener, Helena; Joynt Maddox, Karen E.; Holloway, Robert G.; Li, Yue
Abstract : Importance: The Medicare Bundled Payments for Care Improvement (BPCI) model 3 of 2013 holds participating skilled nursing facilities (SNFs) responsible for all episode costs. There is limited evidence regarding SNF-specific outcomes associated with BPCI. Objective: To examine the association between SNF BPCI participation and patient outcomes and across-facility differences in these outcomes among Medicare beneficiaries undergoing lower extremity joint replacement (LEJR). Design, Setting, and Participants: Observational difference-in-differences (DID) study of 2013–2017 for 330 unique persistent-participating SNFs, 146 unique dropout SNFs, and 14, 028 unique eligible nonparticipating SNFs. Main Outcome Measures: Rehospitalization within 30 and 90 days after SNF admission, and rate of successful discharge from the SNF to the community. Results: Total 636, 355 SNF admissions after LEJR procedures were identified for 582, 766 Medicare patients [mean (SD) age, 76.81 (9.26) y; 424, 076 (72.77%) women]. The DID analysis showed that for persistent-enrollment SNFs, no BPCI-related changes were found in readmission and successful community discharge rates overall, but were found for their subgroups. Specifically, under BPCI, the 30-day readmission rate decreased by 2.19 percentage-points for White-serving SNFs in the persistent-participating group relative to those in the nonparticipating group, and by 1.75 percentage-points for non-Medicaid–dependent SNFs in the persistent-participating group relative to those in the nonparticipating group; and the rate of successful community discharge increased by 4.44 percentage-points for White-serving SNFs in the persistent-participating group relative to those in the nonparticipating group, whereas such relationship was not detected among non-White–serving SNFs, leading to increased between-facility differences (differential DID=−7.62). BPCI was not associated with readmission or successful community discharge rates for dropout SNFs, overall, or in subgroup analyses. Conclusions: Among Medicare patients receiving LEJR, BPCI was associated with improved outcomes for White-serving/non-Medicaid–dependent SNFs but not for other SNFs, which did not help reduce or could even worsen the between-facility differences.